The short-term and long-term effects of Dendrobium officinale leaves polysaccharides on the gut microbiota differ - Ying Yang; Wenyang Tao; Wanyi Zhou; Jingrui Li; Jianrong Xing; Mengfan Luo; Quanqing Tan (Journal of Functional Foods, 2023)
The effect of active substances on the gut microbiota is not immediate, especially for some chronic diseases. This study used an in vitro continuous fermentation system to monitor the changes of gut microbiota in three different colon regions under long-term/short-term DOLP treatment. The results showed that the microbial diversity reached peak on 5th day and remained stable thereafter. Beta diversity analysis showed that the gut microbiota structures of the three regions gradually approached during fermentation. The contents of propionic acid, butyric acid, and valeric acid first increased and then decreased, while isobutyric acid and isovaleric acid first decreased and then increased. Alistipes and Oscillibacter were the key genera in regulating the gut microbiota structure. In summary, Long-term consumption of DOLP has varying effects on the gut microbiota over time, and for the purpose of adjusting the gut microbiota, the most effective duration appears to be continuous consumption for 5 days.